Global burden of calcific aortic valve disease and attributable risk factors from 1990 to 2019 - Yu, Jiaye; Wang, Zhuo; Bao, Qinyi; Lei, Shuxin; You, Yayu; Yin, Zhehui; Xie, Xiaojie (Frontiers in Cardiovascular Medicine, 2022)
Background: Calcific aortic valve disease (CAVD) was highly prevalent among developed countries and caused numerous deaths. Based on the Global Burden of Disease 2019, this study was to comprehensively present epidemiological reports for policy-marker to prevent this disease. Methods: All data were available in the Global Health Data Exchange (GHDx) online. In this study, we analyzed the incidence, prevalence, deaths, DALYs, and several attributable risks of CAVD in the globe, different regions, and 204 countries or territories from 1990 to 2019. We applied the estimated annual percentage changes (EAPCs) to evaluate the trends of CAVD and its attributable risks. In addition, we explored the relationship between the burden of CAVD and covariates. Results: From 1990 to 2019, the incidence and prevalence cases of CAVD gradually increased in the globe, so were CAVD-related death cases and disability-adjusted life years (DALYs). But the age-standardized death rate (ASDR) was relatively stable, even age-standardized DALYs rate gradually declined. Males and elder individuals were more likely to suffer from CAVD. High systolic blood pressure (SBP) was the predominant attributable risk of disease burden but presented a downtrend globally (death: EAPC = -0.68, 95% CI -0.77~-0.59, p < 0.001; DALYs: EAPC = -0.99, 95% CI -1.09 to -0.89, p < 0.001). Alcohol consumption (R=0.79, p < 0.001), smoking prevalence (R=0.75, p < 0.001), calcium (R=0.72, p < 0.001) had positive correlation with the age-standardized incidence rate (ASIR). However, classic monsoon region (R=-0.68, p < 0.001), indoor air pollution (R=-0.73, p < 0.001), mean temperature (R=-0.7, p < 0.001) had negative correlation with ASIR. And medical and healthcare resources presented positive relationship with the burden of CAVD. Conclusion: CAVD displays widely varied spatial distribution around the world and high SDI regions has the highest burden. Age is a powerful factor to develop it and hypertension is a predominant attributable risk factor. Moreover, many measures could be effective to reduce the burden of CAVD.